Secretory pathway research: the more experimental systems the better - Denecke, J.; Aniento, F.; Frigerio, L.; Hawes, C.; Hwang, I.; Mathur, J.; Neuhaus, Jean-Marc; Robinson, D. (My University, 2012)
Transient gene expression, in plant protoplasts or specific plant tissues, is a key technique in plant molecular cell biology, aimed at exploring gene products and their modifications to examine functional subdomains, their interactions with other biomolecules, and their subcellular localization. Here, we highlight some of the major advantages and potential pitfalls of the most commonly used transient gene expression models and illustrate how ectopic expression and the use of dominant mutants can provide insights into protein function.
Keywords: Biological Transport; Fluorescent Dyes/metabolism; Plant Leaves/metabolism/microbiology; Protoplasts/metabolism/ultrastructure; *Research; *Secretory Pathway